(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
In English Language Teaching (ELT), enhancing oral communication skills remains a primary objective, yet challenges persist in effectively achieving this goal through traditional pedagogical methods.